ENVIRONMENTAL CARRYING CAPACITY BASED ON SPATIAL PLANNING - Luthfi Muta'ali (Indonesian Journal of Geography, 2011)
The aims of this research were to examine environmental carrying capacity analyzed basedon aspects of spatial planning and eco-region. The result showed that Kulonprogo Regencyhas low value of environmental carrying capacity and can only support as much as 79.81%of its total population. Analysis of variance showed significant difference of environmentalcarrying capacity of protected and cultivated area. The main factor among 12 variablesdetermining the degree of environmental carrying capacity is man-land ratio (contributed39.72%). Priority should be given to 28 villages or 31.81% of the area with lowenvironmental carrying capacity. Eco-region and spatial plan approaches in environmentalmanagement practice are also strongly recommended.